JENIS-JENIS TUMBUHAN OBAT DI DESA TUAPEJAT KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI SEBAGAI SUMBANGSIH BOOKLET - Uci Arista; Nursyahra; Aulia Afza (EDUBIOLOCK, 2025)
The use of plants as medicinal ingredients is a legacy passed down from our ancerstors that is relatively safe. In addition, the benefits felt by the community regarding medicinal plants are the as medicinal ingredients is a legacy passed down from ancestors that is relatively safe. In addition, the benefits felt by the community regarding medicinal plants are ease of obtaining in the natural surroundings and in the yard. The people of Tuapejat village also cultivate plants as traditional medicine ingredients so that later the result of research on medicinal plants will be found in Tuapejat village, Nort Sipora sub-district, Mentawai islands district, the researcher presented it in the from of a product in the from of a booklet which is presented in simple, concise and clear language. So that knowledge that is informed later will be easier to understand and become additional knowledge for the community. The aim of this study was to determine the types of medicinal plants used by the people of Tuapejat village, Nort Sipora sub-district, Mentawai Islands district. This type of research of qualitative descriptive research with observation and interview metods. This research was conducted in March-April 2024 in Tuapejat Village, Nort Sipora sub-district Mentawai Islands Regency. The result of research conducted in Tuapejat village, Nort Sipora District, Mentawai Islands regency, found 57 types of consististing of 31 families.